Accumulation of flavonoids in the Epilobium angustifolium L. raw material depending on the places of collection and part of the plant - M. S. Antonenko; E. Yu. Zuikova; V. N. Dul; E. L. Malankina (Овощи России, 2023)
The aim. Today we are witnessing the actualization of research on plant sources for the pharmaceutical and food industries. It is caused by a significant increase in demand for these types of resources. Therefore, a variety of case studies aimed at identifying the characteristics of plant resources, are becoming more actual too. In accordance with this need, the present work aims to identify a relationship between the content of flavonoids in the raw material of such important source of plant raw material as Epilobium angustifolium and soil and climatic conditions and group of raw materials.Methods. At the first stage of this work were applied cartographic, geographical methods and methods of geobotanical description of phytocenoses to determine the most suitable locations for the purposes of the study. At the second stage were applied the method of spectrophotometry to determine the amount of flavonoids in terms of rutin and the method of correlation analysis.Results. As a result of the application of these methods were obtained data on the content of flavonoids in the Epilobium angustifolium raw materials, collected in various soil and climatic conditions, as well as in various morphological groups of raw materials. These data were compared by the method of correlation analysis and after that a positive correlation between the content of flavonoids in the leaves and inflorescences of Epilobium angustifolium was found.Conclusion. It was determined, that the content of flavonoids fluctuation, depending on the Epilobium angustifolium place of growth, was 2.05% in the leaves and 2.5% in the inflorescences of this plant. An average positive correlation of 0.65 was found between the content of flavonoids in the leaf and inflorescences of Epilobium angustifolium. However, the correlation between the content of flavonoids and the latitude of Epilobium angustifolium growth wasn’t identified.